Socio-Economic and Rural-Urban Differences in Healthcare and Catastrophic Health Expenditure Among Cancer Patients in China: Analysis of the China Health and Retirement Longitudinal Study - Zhao, Yang; Tang, Shenglan; Mao, Wenhui; Akinyemiju, Tomi (Frontiers in Public Health, 2022)
Objective: In China, cancer accounts for one-fifth of all deaths, and exerts a heavy toll on patients, families, healthcare systems, and society as a whole. This study aims to examine the temporal trends in socio-economic and rural-urban differences in treatment, healthcare service utilization and catastrophic health expenditure (CHE) among adult cancer patients in China. We also investigate the relationship between different types of treatment and healthcare service utilization, as well as the incidence of CHE. Materials and Methods: We analyzed data from the 2011 and 2015 China Health and Retirement Longitudinal Study, a nationally representative survey including 17,224 participants (234 individuals with cancer) in 2011 and 19,569 participants (368 individuals with cancer) in 2015. The study includes six different types of cancer treatments: Chinese traditional medication (TCM); western modern medication (excluding TCM and chemotherapy medications); a combination of TCM & western medication; surgery; chemotherapy; and radiation therapy. Multivariable regression models were performed to investigate the association between cancer treatments and healthcare service utilization and CHE. Results: The age-adjusted prevalence of cancer increased from 1.37% to 1.84% between 2011 and 2015. More urban patients (54%) received cancer treatment than rural patients (46%) in 2015. Patients with high socio-economic status (SES) received a higher proportion of surgical and chemotherapy treatments compared to patients with low SES in 2015. Incidence of CHE declined by 22% in urban areas but increased by 31% in rural areas. We found a positive relationship between cancer treatment and outpatient visits (OR = 2.098, 95% CI = 1.453, 3.029), hospital admission (OR = 1.961, 95% CI = 1.346, 2.857) and CHE (OR = 1.796, 95% CI = 1.231, 2.620). Chemotherapy and surgery were each associated with a 2-fold increased risk of CHE. Conclusions: Significant improvements in health insurance benefit packages are necessary to ensure universal, affordable and patient-centered health coverage for cancer patients in China.